The URV and its function of aligning relative prices - Sicsú, João (Brazilian Journal of Political Economy, 1996)
The Real Plan of stabilization was divided into three phases. The first phase concerned problems of fiscal nature: the governmental deficit. The second one, performed from March to June of 1994, purposed to balance relative prices and remuneration. The third step would knock down the inflation. The article’s aim is to discuss if the device introduced in the second step of the Plan, the Unidade Real de Valor (URV), carried out the goal of aiding the Brazilian economy in the discovery of a balanced vector of relative prices. One carries to the conclusion that the URV did not play its role properly and that the Plan, despite this problem, was successful in the initial period of the third step due to other motives — also discussed in the text. JEL Classification: E31; E52.